A new species of Kalophrynus (Anura: Microhylidae) from the highlands of North-Central Borneo - Das, I.; Haas, A. (National University of Singapore, 2003)
A new species of microhylid of the genus Kalophrynus is described from the Kelabit Highlands of Sarawak at the border with Kalimantan. Kalophrynus eok new species, is compared with congeners from Borneo and other parts of south-east Asia. The new species is diagnosable in showing the following combination of characters: SVL 26.3 mm in the only specimen known, an adult male); snout obtuse, slightly projecting beyond mandible; head wider than long; fingers and toes basally webbed; a single subarticular tubercle on finger IV; inner and outer metarsal tubercles present; dorsum brick-red, with dark interorbital bar, shoulder chevron and transverse body bar irregular in outline and fused with each other; and inguinal ocellus absent.